FEASIBILITY ANALYSIS OF AIR FLOATING DESIGN FOR ELECTRICITY GENERATION - Kalikova, A.; Kusdavletov, S. (Scientific Journal of Astana IT University, 2021)
In the past several decades, there were presented different innovative technologies rather than traditional wind turbines for renewable energy that uses wind kinetic energy and remains in the air through aerodynamic forces. Unlike wind turbines with towers, their systems operate in a flight, and they are connected to a foundation by a cable that either transmits the energy generated at the airfoil or transmits mechanical energy to the ground. Nowadays, there are several existing and developing technologies; however, each of them has limitations and challenges. This work will present an analysis of air floating design for electricity generation at high altitudes. It is a tethered wind turbine with a Balloon system, which has a simple controlling system, relatively higher efficiency, and low-cost technology. The concept of the design is to model the electricity generation device powered by clean renewable energy, mainly wind power. Base on the concept of kite or helium balloon to provide enough buoyancy to keep the device working at certain altitude. To increase the energy conversion efficiency and the feasibility of the device, it is mostly used in the country, open area. Despite high efficiency which needs further investigation, the designed device is moveable, pollution free and little space consumed.